2005
DOI: 10.1063/1.2132520
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of SiC epitaxial layers on Si- and C-face 4H SiC substrates by chemical-vapor deposition

Abstract: High-quality Schottky junctions have been fabricated on n-type 4H SiC epitaxial layers grown by chemical-vapor deposition on C-and Si-face substrates in order to understand the effect of growth direction on the growth mechanism and formation of defects. Atomic force microscopy analysis showed dramatic differences between the surfaces of SiC epilayers grown on C and Si faces. There was a significant step bunching in the SiC grown on Si-face substrates. Current-voltage, capacitance-voltage, and deep-level transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The reduction of off-angle is beneficial in both reducing the substrate price and promoting the conversion of BPDs into threading edge dislocations [5][6][7]. Additional studies have shown C-face growth is less susceptible to step bunching during both epitaxial growth and post-implantation anneal [6,[8][9][10]. In view of the above advantages, epitaxial growth on 41 off-axis C-face 4H-SiC substrates has been investigated using a horizontal hot-wall chemical vapor deposition (CVD) reactor.…”
Section: Introductionmentioning
confidence: 98%
“…The reduction of off-angle is beneficial in both reducing the substrate price and promoting the conversion of BPDs into threading edge dislocations [5][6][7]. Additional studies have shown C-face growth is less susceptible to step bunching during both epitaxial growth and post-implantation anneal [6,[8][9][10]. In view of the above advantages, epitaxial growth on 41 off-axis C-face 4H-SiC substrates has been investigated using a horizontal hot-wall chemical vapor deposition (CVD) reactor.…”
Section: Introductionmentioning
confidence: 98%
“…5,6) Recent studies have indicated that the C-face is practically very important and it is different from the Siface in many aspects. 3,[7][8][9][10][11] Thus far, no reliable dislocationmapping technique is available for the C-face except X-ray topography (XRT) that is expensive and time-consuming. Therefore, it is of great importance to develop a dislocationrevealing chemical etching for the C-face that works like molten KOH etching for the Si-face.…”
mentioning
confidence: 99%
“…On the other hand, the magnitude of the leakage current is lower in the Schottky junctions formed on the epilayers grown on the wafers than that in the junctions formed on the wafers, as shown in Fig. 7 [24]. This may be eventually due to the lower density of basal plane dislocations, microtubes, micropipes, pits, screw dislocations, etc., in the epitaxial layers.…”
Section: Resultsmentioning
confidence: 78%
“…8 for a schematic diagram) on the epitaxial layers grown on the C-face substrate were studied using C-V method in which the calculation of carrier concentration (n), barrier heights (F b ), etc., is given extensively elsewhere [24]. The C-V mapping studies revealed that the junction barrier height is lower in the junctions formed at the edges of the samples due to the formation of carrot-like structures, which degrade the quality of the layers.…”
Section: Article In Pressmentioning
confidence: 99%